Penerapan Knowledge Management Pada Universitas Negeri Padang - Chichi Andriani (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2017)
The purpose of this research was to explore the application of knowledge management at Universitas Negeri Padang. The population in this research are all lecturer at Universitas Negeri Padang. Sampling used by of stratified random sample with proportional sampling and get to the number 132 sample. The data in this research were collected through questionnaires and analyzed by descriptive analysis method and the rate of application of acquired knowledge management used by the level of achievement according to the analysis Forster. The results showed that the level of application of knowledge management is measured through the variable people (experience) obtained of 68.8%, the variable process (standard operational procedure) obtained of 64.4%, the variable technology obtained of 78% and for the implementation of knowledge management (people, process and technology) in total obtained value is 70.4%. TCR results obtained on each of the variables and the total value that the level of application of knowledge management at Universitas Negeri Padang are in the level of developing potential. It is indicated for knowledge management is still not yet applied by al members of the organization at Universitas Negeri Padang because had a influenced by cultural, term of office, faculty’s age and other factors.